A Late Diagnosed Neurofibromatosis Case During Preoperative Evaluation For Scoliosis - YAVUZ, DİLEK (My University, 2023)
Objective Neurofibromatosis type 1 is an autosomal dominant inherited neurocutaneous condition characterized with multipl cafe-au-lait spots, neurofibromas, predisposition to malignancies, and the incidence of disease is 1:3000. Patients are diagnosed according to diagnostic criteria and 97% of the patents meet the criteria before 8 years of old. Diagnosis and follow-up of patients for manifestations of neurofibromatosis is important for early diagnosis and treatment of malignancies. Case Twenty-one year old female patient admitted to neurosurgery outpatient clinic with complaint of scoliosis. She was consultated to endocrinology clinic for low bone mineral density levels and osteoporotic findings in vertebral x-ray examination. In physical examination she was short statured and she had growth retardation. She had multipl cafe-au-lait spots and scoliosis. On right lower limb, she had a brown lesion and after consultation with dermatology clinic it was considered as plexiform neurofibroma. Her bone mineral density level (BMD) in L1-L4 was 1.006, z score was -0.7, femur neck BMD was 0.669 z score was -2.1. Her osteocalcin level was 21.5 ng/ml (9-42), c-telopeptide was 0.23. Hypophysial hormones were evaluated and her IGF-1 level was found to be low according to age reference range. Insulin tolerance test was performed and her growth hormone was found to be 0.206 when her blood glucose was 36 mg/dl. In family history, her mother and brother were also learnt to have multiple cafe-au-lait spots and in physical examination her mother had cutaneous neurofibromas. Neurofibromatosis diagnosis was confirmed after genetic consultation and genetic test. Hamartomatous lesion in both basal ganglia and thalamus and in right frontal lobe were found in cranial magnetic resonaunce imaging (MRI). In abdominal MRI, neurofibromas in right coxofemoral articulation and right acetabulum were found. Her urine metabolites were examined for pheochromacytoma and found in normal levels. Follow-up visits were planned and she was concultated to relevant departments. Her mother and brother were also diagnosed as neurofibromatosis. Discussion and Conclusion Patients with neurfibromatosis have a high predisposition to develop both benign and malign tumours. Although most of the manifestations effect the nervous system, multiple organs and tissues can be affected. Patients can present with different clinical symptoms to different clinics so being aware of the different clinical manifestations of the disease is important for prompt diagnosis. DOI: 10.1530/endoabs.90.EP201
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Endokrinoloji ve Metabolizma Hastalıkları; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Endocrinology and Metabolic Diseases; Health Sciences; Klinik Tıp (MED); Klinik Tıp; ENDOKRİNOLOJİ VE METABOLİZMA; TIP, GENEL & DAHİLİ; Clinical Medicine (MED); CLINICAL MEDICINE; ENDOCRINOLOGY & METABOLISM; MEDICINE, GENERAL & INTERNAL; Genel Sağlık Meslekleri; Patofizyoloji; Temel Bilgi ve Beceriler; Değerlendirme ve Teşhis; Endokrin ve Otonom Sistemler; Dahiliye; Aile Sağlığı; Endokrinoloji, Diyabet ve Metabolizma; Tıp (çeşitli); Genel Tıp; Endokrinoloji; Yaşam Bilimleri; General Health Professions; Pathophysiology; Fundamentals and Skills; Assessment and Diagnosis; Endocrine and Autonomic Systems; Internal Medicine; Family Practice; Endocrinology, Diabetes and Metabolism; Medicine (miscellaneous); General Medicine; Endocrinology; Life Sciences